Information resources: analysis and classification - Myliutchenko, I.O.; Onopko, B.V. (Radiotekhnika, 2018)
The category of "information resource" in the field of information security is considered based on the research of the processes of formation, use and protection of information resources of different levels. A variant of classification of information resources, obtained as a result of analysis and generalization of classification characteristics from many sources, is proposed.